2001
DOI: 10.1007/s00454-001-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Skin Triangulation

Abstract: Abstract. This paper describes an algorithm for maintaining an approximating triangulation of a deforming surface in R 3 . The surface is the envelope of an infinite family of spheres defined and controlled by a finite collection of weighted points. The triangulation adapts dynamically to changing shape, curvature, and topology of the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 14 publications
0
64
0
Order By: Relevance
“…Cheng et. al [9] maintained an approximating triangulation of a deforming skin surface. Simplex subdivision schemes are used to generate tetrahedral meshes for molecular structures in solving the Poisson-Boltzmann equation [22].…”
Section: Molecular Surface Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheng et. al [9] maintained an approximating triangulation of a deforming skin surface. Simplex subdivision schemes are used to generate tetrahedral meshes for molecular structures in solving the Poisson-Boltzmann equation [22].…”
Section: Molecular Surface Approximationmentioning
confidence: 99%
“…We obtain the unit sphere triangulation from [45]. For each vertex q on the triangulated atom surface M N , is computed using the point projection algorithm, where n(q) is the spherical normal at q. for each triangle vertex q ∈ S N ∩S N 0 do { • compute P M N 1 (q, n(q)), and then compute - (9) • } Table 2 shows the minimal error of our level one surface for a residue and a chain from Ribosome 30S, where e(M) is defined as . It can be observed that the error decreases as p increases.…”
Section: Minimal Error Of Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin surface is the envelope of families of an infinite number of evolving spheres [37]. It satisfies many desirable mathematical properties.…”
Section: Visualizing Biomolecular Surfacesmentioning
confidence: 99%
“…The skin surface is not C 2 -continuous, but its maximum normal curvature, κ, is continuous. This property is exploited by Cheng et al [1], who describe an algorithm that constructs a triangular mesh representing the skin surface. In this mesh, the sizes of edges and triangles are inversely proportional to the maximum normal curvature.…”
Section: Introductionmentioning
confidence: 99%